A knowledge management approach to compare and develop the ASEAN University Credit Transfer System in Thailand - Chayamarnie Bhiriyawanit (2019)
© IEOM Society International. This paper outlines a comparative study between the European Credit Transfer System (ECTS) and the ASEAN Credit Transfer System (ACTS). In 2015, ASEAN member countries will form the ASEAN Economic Community (AEC), a region promoting economic integration and the subsequent free flow of people, trade and culture. The AEC will have significant impacts on higher education across the ASEAN region, and this research investigates how knowledge management techniques can be utilized to respond effectively to the forthcoming ACTS. The ACTS is a tool created to enhance and facilitate credit transfer allocation between members of the ASEAN University Network (AUN) and will present particular challenges for Thailand's university administration and management. The paper presents a case study from Thailand, and leverages Common Knowledge Acquisition and Documentation Structuring (CommonKADS) to capture appropriate knowledge from Europe, where a successful Europe-wide credit transfer system already exists. The paper undertakes a comparative study between the ECTS and the proposed ACTS. The case study is based within the Faculties of Law, at Chiang Mai University (CMU), Thailand, and University Lumière Lyon 2, France. In Thailand, a requirement exists to prepare and provide a new framework to ensure its Credit Transfer System (CTS) procedure correlates with the needs of the ASEAN University Network CTS (AUN-CTS). The AUN-CTS is a particular aspect of the AUN, which members must adhere to. This research therefore studies the importance and usefulness of the ECTS in comparison to the ACTS and more importantly, captures existing and relevant knowledge from the ECTS to raise awareness and enhance the credit transfer procedure of the CMU law faculty. Results show that utilizing knowledge to create a successful credit transfer allocation will facilitate increased student and faculty exchange, including training programs and worker mobility.